Sistem Informasi Manajemen Pendidikan Islam bagi Staf Administrasi Madrasah - Siti Juariah; Muntako Muntako; Ali Muhdi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The rapid development of information and communication technology has driven Islamic educational institutions, including madrasah, to adopt management information systems (MIS) to support administrative governance. This article examines the concept of MIS in Islamic education, its effectiveness in improving the performance of administrative staff, the factors that determine the success or failure of MIS implementation, and the strategic role of madrasah administrative staff as the primary operators of integrated data systems such as EMIS, SIMPATIKA, and DAPODIK. This study employs a qualitative descriptive method through a literature review (library research), analyzing books, journal articles, and government regulations relevant to MIS in Islamic education. The findings show that MIS implementation significantly improves work efficiency, data accuracy, information accessibility, service quality, and managerial decision-making, while its success depends on adequate human resources, technological infrastructure, leadership commitment, continuous training, and system integration. Conversely, implementation failure is commonly caused by limited resources, resistance to change, low technological literacy, technical problems, and weak monitoring mechanisms. Empirical evidence from several madrasah-based studies confirms that the readiness and competence of administrative staff, rather than technological sophistication alone, are the key determinants of MIS success at the operational level. These findings reinforce the urgency of positioning administrative staff as the central unit of analysis in future research on Islamic education management information systems.